Does dietary incorporation level of pea protein isolate influence the digestive system morphology in rainbow trout (Oncorhynchus mykiss)? - Demirci, Beste; Terzi, Funda; Kesbic, Osman Sabri; Acar, Umit; Yilmaz, Sevdan; Kesbic, Fevziye Isil (Wiley, 2021)
AbstractIn the present study, fish meal (FM) was replaced by pea (Pisum sativum) protein (PP) in diet for Rainbow trout (Oncorhynchus mykiss) at levels of 0% (PP0), 25% (PP25), 50% (PP50), 75% (PP75) and 100% (PP100), and the effect of dietary PP level on the digestive system tracts and liver was investigated by micromorphological and histopathological evaluations. Morphometric measurements (mm 100g fish−1) of the liver width and stomach length in rainbow trout were found to be significantly larger (p <0.05) in fish with high‐level pea protein as the main protein source (PP75, PP100) compared to the low‐level PP replacement group (PP25). No significant differences were found in morphometric measurements for pyloric caecum and intestines among treatment groups, whereas the number of the caecum of fish fed the PP25 diets significantly increased over the control (PP0) (p<0.05). In the histological examination of the liver, mild hydropic and vacuolar degeneration was observed in all experimental groups except PP0 and PP25. The measurements of pyloric caecum fold height, enterocyte length and width of tunica muscularis of the high‐level pea protein groups of PP75 and PP100 were significantly higher (p <0.05) compared to the control group. In conclusion, 25% substitution of PP can be suggested for FM in trout diets, because the findings of the present study provided evidence that the digestive system improved by increasing the number of pyloric caecum at this replacement level.
Keywords: Liver; Oncorhynchus mykiss; Animals; Diet; Pea Proteins